Throughput analysis on dynamic spectrum allocation technique to mitigate interference on LTE heterogeneous network - Othman, Nurzati Iwani; Ismail, Ahmad Fadzil; Hasan, Muhammad Kamrul; Badron, Khairayu; Hashim, Wahidah (Science & Engineering Research Support Society (SERSC), 2018)
The use of mobile devices has gradually increased over time. It has become a necessity for people to own mobile devices in order to communicate with others all around the world. With increasing number of users, the LTE network service providers need to think of a way on how to enhance their service so that users can experience faster internet experience without any disruption from the network. In a heterogeneous network that consists of several base stations and scores of users, cross-tier interference is bound to occur. Cross-tier interference can cause loss of signal and drop calls. In this paper, a Dynamic Spectrum Allocation (DSA) technique was proposed and implemented in a LTE network configuration. At this juncture, the study only focuses on the segment involving communication downlink. Software development toolkit GNU Radio was used in the assembly of the network configurations. Throughput comparison was then made against a normal LTE network configuration. The throughputs of both configurations were computed and assessed. Configuration embedded with DSA managed to achieve higher throughput. The findings suggest that DSA is a technique capable of mitigating interference for LTE network.